2010
DOI: 10.1523/jneurosci.3800-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsomedial Pathway Is Not Just for Reaching: Grasping Neurons in the Medial Parieto-Occipital Cortex of the Macaque Monkey

Abstract: Brain control of prehension is thought to rely on two specific brain circuits: a dorsomedial one (involving the areas of the superior parietal lobule and the dorsal premotor cortex) involved in the transport of the hand toward the object and a dorsolateral one (involving the inferior parietal lobule and the ventral premotor cortex) dealing with the preshaping of the hand according to the features of the object. The present study aimed at testing whether a pivotal component of the dorsomedial pathway (area V6A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
153
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 179 publications
(180 citation statements)
references
References 46 publications
25
153
1
1
Order By: Relevance
“…We have found that ϳ50% of V6A neurons are modulated by gaze direction and depth of fixation when monkeys perform saccades and fixate targets at different locations, in peripersonal as well as in extrapersonal space. We have found responses that in most cases were higher for fixating targets located within the reaching distance, thus supporting the proposed role of V6A in monitoring reach-to-grasp actions (Galletti et al, 2003;Fattori et al, 2009Fattori et al, , 2010Hadjidimitrakis et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…We have found that ϳ50% of V6A neurons are modulated by gaze direction and depth of fixation when monkeys perform saccades and fixate targets at different locations, in peripersonal as well as in extrapersonal space. We have found responses that in most cases were higher for fixating targets located within the reaching distance, thus supporting the proposed role of V6A in monitoring reach-to-grasp actions (Galletti et al, 2003;Fattori et al, 2009Fattori et al, , 2010Hadjidimitrakis et al, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Finally, our results provided further evidence against the hypothesis of a clear‐cut distinction between a dorsomedial (e.g., SPOC, medial intraparietal area MIP, and PMd) and dorsolateral (e.g., hAIP and PMv) pathways, specialized for reaching‐only and reach‐to‐grasp actions, respectively, as reported in a series of recent studies on human and nonhuman primates (Fattori et al. 2009, 2010; Cavina‐Pratesi et al. 2010; Monaco et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2003) in nonhuman primates, and well documented by Fattori et al. (2009, 2010). Reaching‐only and reach‐to‐grasp actions could be better characterized by temporal, rather than spatial criteria across planning and execution stages of the action, as also suggested by a recent study of Begliomini et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V6A is a parietal area receiving visual information (Galletti et al, 1996;1999;Gamberini et al, 2009) as well as somatosensory-and movement-related signals relative to reach and grasp actions (Galletti et al, 1997;Fattori et al, 2001;Breveglieri et al, 2002;Fattori et al, 2005;Fattori et al, 2009;Fattori et al, 2010). The present study was designed to determine whether and how the vision of the moving limb influences the activity of V6A neurons during reaching movements.…”
Section: Discussionmentioning
confidence: 99%